Analysis of ground settlement in land reclamation project - Saw, Ohnmar Oo (2017)
Land reclamation has become widely used in recent years due to the increasing demand for space. In most instances of land reclamation, ground improvement works are required due to the highly compressible soft soil. The installation of vertical drains with preloading is a commonly used method of ground improvement.